Relasi Badan Permusyawaratan Desa dengan Pemerintah Desa Dalam Pembangunan di Desa Tenaru Kecamatan Driyorejo Kabupaten Gresik Provinsi Jawa Timur - Karolina R.S Wenggi; Muchammad Rezal Ardiansyah; Dedy Pribadi Uang (Jurnal Politik Pemerintahan Dharma Praja, 2025)
This study explores the relationship between the Village Consultative Body (BPD) and the Village Government in Tenaru Village, which has not been functioning optimally. This is evident from the failure to implement several development programs, despite their inclusion in the Village Medium-Term Development Plan (RPJMDes). These issues highlight weak coordination and limited community participation in village development projects. The aim is to analyze the dynamics between the BPD and the Village Government and identify factors affecting this relationship in Tenur Village, Driyorejo District, Gresik Regency. Using descriptive qualitative methods and an inductive approach, data were gathered through observation, interviews, and document review, followed by data reduction, presentation, inference, and triangulation. The analysis indicates that: (1) the relationship is generally unequal, mainly due to the dominance of the Village Government, which leads to the BPD being less active in government affairs and community aspiration efforts. This is caused by budget limitations and the busy schedules of BPD members outside their village duties. (2) Factors encouraging cooperation between the BPD and the Village Government in facilitating development include: (a) the lack of a specific program to gather villagers' aspirations; (b) insufficient budget for BPD members' allowances; and (c) the backgrounds of BPD members. To improve this, it is suggested to strengthen the BPD’s role through developing Village-Owned Enterprises (BUMDes), collaborating to explore village potential, engaging with the private sector, increasing capacity through training, and conducting comparative studies with villages where the BPD-Government relationship works effectively.